ETHNIC SELF AS REFLECTION OF INNER WORLD - Anna S. Sobilskaya (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a comparative analysis of the ideas regarding the ethnic identity and the ethnic awareness as parts of the personal ethnic self in the national and international psychology. When working on the category of the ethnic identity and the ethnic awareness authors typically take into view the national approaches while international viewpoints are equally interesting. Summarization of the international experience shows that the ethnic identity appears as a socio-cultural phenomenon.